Recyclable multilayer structure for fluid delivery, dispensing or storage applications
By using a multi-layer structure, the water-soluble barrier layer is used to maintain the barrier performance of the hose in a high temperature and oxidation environment, and is easy to deal with after recycling, the problem of hoses being unable to be reused in the prior art is solved and global change is reduced Warm pressure.
Patent Information
- Application Number
- CN202380050509.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-04
- Filing Date
- 2023-07-04
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively recycle hoses in scrapped motor vehicles, especially in high temperature and oxidation environments, which leads to the inability to reuse of hoses, increasing the pressure of global warming.
A multi-layer structure is adopted, which consists of an outer layer, a barrier layer and an inner layer. The outer and inner layers are made of aliphatic polyamide, and the barrier layer is water-soluble at a temperature less than or equal to 150°C, which can provide similar barrier properties to the EVOH structure while being easy to handle during the recycling process.
It realizes the barrier performance of the hose under high temperature and oxidation environment, and can be effectively recycled and reused after recycling, reducing the impact on the environment.
Smart Images

Figure BDA0005214192440000261
Abstract
Description
[0001] The present invention relates to recyclable multilayer structures for use in fluid transport, dispensing or storage applications. Prior art
[0002] Every year, millions of motor vehicles are scrapped around the world. End-of-life vehicles (ELVs) contain a large number of toxic and polluting products (liquid or solid): waste oil, batteries, air conditioning fluid, explosive substances in airbags, etc. If handled under inappropriate conditions, these wastes may cause ground and water pollution and even accidents. Therefore, ELVs are considered hazardous waste.
[0003] A large number of vehicle components can be collected and recycled in the form of second-hand spare parts or raw materials. Parts intended for reuse (headlights, indicator lights, engines, radiators, starters, hoods, fenders, doors, etc.) are dismantled and stored for resale.
[0004] Non-recyclable debris and parts (ferrous and non-ferrous metals, plastics, glass, rubber, etc.) are crushed for reuse or sent to landfill.
[0005] European Directive 2000 / 53 / Ec on end-of-life vehicles stipulates that from 2015 onwards the reuse and recycling level for each vehicle must be 95% by weight.
[0006] This means that only 5% by weight is final waste, i.e. waste that is not suitable for processing under current technical and economic conditions and which will be incinerated or disposed of in special storage centres.
[0007] Reuse and reuse 95% of the weight subject to the following:
[0008] Energy recovery: Utilization of waste (oil, tires, plastics, etc.) as a means of producing energy through direct incineration, either together with other waste or separately;
[0009] Material reuse: Reuse or repurposing: the reuse of parts that retain the same purpose and are not transformed; or recycling: the operation aimed at introducing materials from waste into the production cycle, replacing the original materials in whole or in part.
[0010] Motor vehicles contain a large number of hoses, in particular for conveying air, oil (for example for cooling an automatic transmission (transmission oil cooler (TOC)), water, urea solution, glycol-based coolants, fuels such as gasoline (in particular biogasoline) or diesel (in particular biodiesel) or hydrogen.
[0011] These hoses can be single-layer and / or multi-layer tubular structures, in particular based on polyamide.
[0012] When a motor vehicle is scrapped, some of the hoses within the vehicle may themselves be too degraded to be reused in tubular form without risk or undue degradation of operating performance.
[0013] In particular, tubes, especially under-the-hood tubes, are in a harsh thermo-oxidative environment due to the heat generated by the engine (typically up to 150°C) and the presence of air and therefore oxygen. Every 10°C increase in temperature typically halves the life of the tube, and degradation of certain additives to the tube (e.g., stabilizers) is similar.
[0014] Furthermore, hoses for conveying fuels, for example polyamide hoses containing plasticizers, have lost most of the plasticizers at the end of their service life and the polyamide originally present, of which it is composed, may have partially depolymerized and / or degraded and lost most of its stabilizers, which makes it impossible to reuse them without risk.
[0015] To date, hoses from scrapped motor vehicles have not been reused and are usually incinerated. This further contributes to global warming, the reduction of which has become one of the major challenges of the 21st century.
[0016] Currently, structures with ethylene vinyl alcohol (EVOH) barrier layers are difficult to recycle because the PA / EVOH blends obtained after grinding and re-blending are less efficient than the expected specifications in terms of mechanical properties and present safety risks.
[0017] In particular, after extrusion with the PA / EVOH blends obtained, the final parts contain brittle areas (presence of cracks and premature failures) representing a safety risk, in particular with regard to fuels.
[0018] Furthermore, many motor vehicle manufacturers have set themselves more or less long-term goals to recycle 100% of the vehicles they produce in order to achieve a zero environmental impact.
[0019] Therefore, in the context of sustainable development, it would be interesting to use structures with barrier layers that can be easily disposed of in recycling processes.
[0020] International patent application WO 2009 / 083525 describes PVOH as having barrier properties to grease and gas, but in the absence of water. Specifically, the barrier properties of PVOH to grease and gas disappear when in contact with liquid water or even water vapor under "hot" conditions (38°C and 90% RH). These properties will be lost if the composite is washed with a solvent that can dissolve the water-blocking film, or if the composite is used at a temperature above the melting point of the water-blocking film.
[0021] To solve this problem, the international patent application uses PVOH with a molecular weight greater than 13,000 and a degree of hydrolysis greater than 81%, and grafts fatty acids with aliphatic chains containing at least 12 carbon atoms on the surface, thereby providing a film with barrier properties against water, grease, gas and water vapor.
[0022] International patent application WO 2008 / 057763 describes a tube having at least five symmetrical polyamide layers, wherein the central layer is made of EVOH or PVOH, in order to avoid tube breakage problems. The thickness of the barrier layer is between 210 and 280 μm.
[0023] PVOH is mentioned, but no examples are given, nor is its recyclability stated.
[0024] Therefore, there is a need to propose structures with barrier properties to fuels such as gasoline (especially biogasoline), diesel (especially biodiesel) or gases such as hydrogen, carbon dioxide, oxygen and nitrogen, which are close to the structures currently proposed, but have optimal recyclability that cannot be provided by structures with EVOH barrier layers.
[0025] Therefore, the present invention relates to a recyclable multilayer structure for transporting, distributing or storing fluids, in particular for distributing or storing fluids, comprising from the outside to the inside:
[0026] 1) An outer layer (I) made of polyamide, in particular aliphatic polyamide, comprising a composition comprising:
[0027] a) 41 to 100% by weight of at least one polyamide having a C / N ratio of greater than 7, preferably greater than 8, in particular an aliphatic polyamide,
[0028] b) 0 to 10% by weight of at least one polyamide, different from the aforementioned polyamides, having a C / N ratio of less than 10, preferably less than 8, in particular an aliphatic polyamide,
[0029] c) 0 to 30% by weight of at least one impact modifier,
[0030] d) 0 to 5% by weight of at least one additive,
[0031] e) 0 to 14% by weight of at least one plasticizer,
[0032] The sum of the components a)+b)+c)+d)+e) is equal to 100% by weight.
[0033] 2) a barrier layer (II) which is water-soluble at a temperature of less than or equal to 150° C., in particular less than or equal to 120° C.;
[0034] 3) Inner layer (III):
[0035] It is made of polyamide, especially aliphatic polyamide, and comprises a composition comprising:
[0036] a) 41 to 100% by weight of at least one polyamide having a C / N ratio of greater than 7, preferably greater than 8, in particular an aliphatic polyamide,
[0037] b) 0 to 10% by weight of at least one polyamide, different from the aforementioned polyamides, having a C / N ratio of less than 10, preferably less than 8, in particular an aliphatic polyamide,
[0038] c) 0 to 30% by weight of at least one impact modifier,
[0039] d) 0 to 5% by weight of at least one additive,
[0040] e) 0 to 14% by weight of at least one plasticizer,
[0041] The sum of the components a) + b) + c) + d) + e) is equal to 100% by weight;
[0042] and / or
[0043] Layer (IV) which essentially comprises at least one polyamide of aliphatic type or consisting of more than 75% aliphatic units, said aliphatic polyamide being chosen from:
[0044] - polyamides, denoted A, whose average number of carbon atoms per nitrogen atom, denoted CA, is from 4 to 8.5, advantageously from 4 to 7;
[0045] - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5;
[0046] - polyamides, denoted C, whose average number of carbon atoms per nitrogen atom, denoted CC, ranges from 9 to 18, advantageously from 10 to 18;
[0047] Layer (IV) is adjacent to layer (II) if layer (III) is also present and layer (III) is the innermost; or if layer (III) is not present, layer (IV) is the innermost.
[0048] Therefore, the inventors unexpectedly discovered that the use of a barrier layer that is water-soluble at a temperature of less than or equal to 150°C (in particular, less than or equal to 120°C) in a multilayer structure for transporting, distributing or storing fluids not only enables the barrier properties of the structure to be similar to those of the structures made of EVOH in the prior art, but also allows the structure to be recycled without any performance loss in mechanical properties relative to the expected specifications, especially after grinding, which is not possible for structures whose barrier materials are made of EVOH.
[0049] In one embodiment, the aliphatic polyamide is selected from:
[0050] - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5;
[0051] - polyamides, denoted C, having an average number of carbon atoms per nitrogen atom, denoted CC, ranging from 9 to 18, advantageously from 10 to 18.
[0052] The term "recyclable" means that the tubular structure, after use and therefore after transporting, distributing or storing fluids, can be reused, in particular after being ground and washed with hot water, i.e. used in a parts (in particular new tubular structures) manufacturing process (in particular by extrusion), while obtaining good mechanical properties, in particular cold impact, low flexural modulus and high elongation at break, unlike the recycling of structures comprising an EVOH layer.
[0053] Grinding to a size of 1 mm to 2 cm is performed according to conventional techniques used by those skilled in the art.
[0054] Said reuse of said used tubular structure may or may not be done with mixing with virgin material.
[0055] The term "multilayer structure" means, for example, a tank, a hose or a pipe comprising or consisting of several layers (especially two layers), and excluding films or particles.
[0056] The term "fluid" denotes a gas or liquid used in the automotive industry, in particular air, oil (for example for cooling automatic transmissions (TOC, transmission oil cooler)), water, urea solution, glycol-based coolants, or fuels such as gasoline (in particular alcohol-blended gasoline, biogasoline) or diesel (in particular biodiesel) or hydrogen, and a fluid selected from carbon dioxide, oxygen and nitrogen.
[0057] In one embodiment, the fluid represents a fuel, in particular gasoline, in particular alcohol-blended gasoline, biogasoline; or diesel, in particular biodiesel.
[0058] In one embodiment, the fluid represents hydrogen.
[0059] Composition of the outer layer (I)
[0060] Polyamidea)
[0061] The at least one polyamide a) of layer (I) is a polyamide having a C / N ratio greater than 7, preferably greater than 8, in particular an aliphatic polyamide.
[0062] It may be aliphatic, aromatic or semi-aromatic.
[0063] Advantageously, it is aliphatic.
[0064] The nomenclature used to define polyamides is described in the standard ISO 1874-1:2011 "Plastics - Polyamide (PA) molding and extrusion materials - Part 1: Designation" and is familiar to the person skilled in the art.
[0065] According to the present invention, the term "polyamide" means homopolyamide or copolyamide.
[0066] Advantageously, the polyamide is semi-crystalline.
[0067] For the purposes of the present invention, throughout the description, the term "semi-crystalline polyamide" means a polyamide having a melting point (Tm) and a heat of fusion ΔH>25 J / g, in particular>40 J / g, especially>45 J / g, and also having a glass transition temperature (Tg) determined by DSC at a heating rate of 20 K / min according to standards ISO 11357-1:2016 and ISO11357-2 and 3:2013.
[0068] The at least one polyamide, when it is aliphatic, is obtained from the polycondensation of at least one lactam, or from the polycondensation of at least one amino acid, or from the polycondensation of at least one diamine Xa with at least one dicarboxylic acid Yb.
[0069] When the at least one aliphatic polyamide is obtained by polycondensation of at least one lactam, the at least one lactam may be selected from C 6 To C 18 , preferably C 10 To C 18 , more preferably C 10 To C 12 Lactam. C 6 To C 12 The lactam is in particular caprolactam, decanolactam, undecanolactam or laurolactam.
[0070] When the at least one aliphatic polyamide is obtained by polycondensation of at least one lactam, it may comprise one lactam or several lactams.
[0071] Advantageously, said at least one aliphatic polyamide is obtained by polycondensation of a single lactam, and said lactam is chosen from laurolactam and undecanolactam, advantageously laurolactam.
[0072] When the at least one aliphatic polyamide is obtained by polycondensation of at least one amino acid, the at least one amino acid may be selected from C 6 To C 18 , preferably C 10 To C 18 , more preferably C 10 To C 12 Amino acids.
[0073] C 6 To C 12 The amino acids are in particular 6-aminocaproic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 10-aminoundecanoic acid, 12-aminododecanoic acid and 11-aminoundecanoic acid and derivatives thereof, in particular N-heptyl-11-aminoundecanoic acid.
[0074] When the at least one aliphatic polyamide is obtained from the polycondensation of at least one amino acid, it may comprise a single amino acid or several amino acids.
[0075] Advantageously, the aliphatic polyamide is obtained by polycondensation of a single amino acid, and the amino acid is chosen from 11-aminoundecanoic acid and 12-aminododecanoic acid, advantageously 11-aminoundecanoic acid.
[0076] When the at least one aliphatic polyamide is composed of at least one C 4 -C 36 , priority C 5 -C 18 , priority C 5 -C 12 , more priority C 10 -C 12 The diamine Xa is mixed with at least one C 4 -C 36 , priority C 6 -C 18 , priority C 6 -C 12 , more priority C 10 -C 12 When the polycondensation of the diacid Yb is obtained, then the at least one diamine Xa is an aliphatic diamine and the at least one diacid Yb is an aliphatic diacid.
[0077] The diamine may be linear or branched. Advantageously, it is linear.
[0078] The at least one C 4 -C 36The diamine Xa may be chosen in particular from 1,4-butanediamine, 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine and 1,18-octadecamethylenediamine, octadecenediamine, eicosanediamine, docosanediamine and diamines obtained from fatty acids.
[0079] Advantageously, the at least one diamine Xa is C 5 -C 18 and is selected from 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine and 1,18-octadecamethylenediamine.
[0080] Advantageously, the at least one diamine Xa is C 5 -C 12 and in particular selected from 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine and 1,12-dodecamethylenediamine.
[0081] Advantageously, the at least one C 6 -C 12 The diamine Xa is in particular selected from 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine and 1,12-dodecamethylenediamine.
[0082] Advantageously, the diamine Xa used is C 10 To C 12 Diamines, in particular selected from 1,10-decamethylenediamine, 1,11-undemethylenediamine and 1,12-dodecamethylenediamine.
[0083] The at least one C 4 -C 36 The dicarboxylic acid Yb may be chosen from: succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid and diacids obtained from fatty acids.
[0084] The diacid may be linear or branched. Advantageously, it is linear.
[0085] Advantageously, the at least one dicarboxylic acid Yb is C 6 -C 18 The acid is selected from the group consisting of adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid and octadecanedioic acid.
[0086] Advantageously, the at least one dicarboxylic acid Yb is C 6 -C 12 The acid is selected from adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid and dodecanedioic acid.
[0087] Advantageously, the at least one dicarboxylic acid Yb is C 10 -C 12 and is selected from the group consisting of sebacic acid, undecanedioic acid and dodecanedioic acid.
[0088] When the aliphatic polyamide is obtained from the polycondensation of at least one diamine Xa and at least one dicarboxylic acid Yb, it may then comprise a single diamine or several diamines and a single dicarboxylic acid or several dicarboxylic acids.
[0089] Advantageously, the aliphatic polyamide is obtained by polycondensation of a single diamine Xa with a single dicarboxylic acid Yb.
[0090] In one embodiment, the aliphatic polyamide a) is selected from PA610, PA612, PA516, PA1010, PA1012, PA1014, PA1212, PA1214, PA11 and PA12.
[0091] Advantageously, it is chosen from PA612, PA516, PA1010, PA1012, PA1014, PA1212, PA1214, PA11 and PA12, in particular PA11 and PA12.
[0092] The at least one semi-aromatic polyamide or polyphthalamide (PPA) may be a homopolyamide or a copolyamide.
[0093] When it is in the form of a homopolyamide, it has the formula XAr or Ar'Y.
[0094] XAr represents a unit obtained by polycondensation of a diamine X and an aromatic dicarboxylic acid Ar, wherein the diamine X is C 6 -C 36 , priority C 6 -C 18 , priority C 6 -C 12 , more priority C10 -C 12 .
[0095] The diamine may be linear or branched. Advantageously, it is linear.
[0096] The at least one C 6 -C 36 The diamine X may be chosen in particular from 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine and 1,18-octadecamethylenediamine, octadecenediamine, eicosanediamine, docosanediamine and diamines obtained from fatty acids.
[0097] Advantageously, the at least one diamine X is C 6 -C 18 and is selected from 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine, and 1,18-octadecamethylenediamine.
[0098] Advantageously, the at least one C 6 -C 12 The diamine X is in particular selected from 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine and 1,12-dodecamethylenediamine.
[0099] Advantageously, the at least one C 6 -C 12 The diamine X is in particular selected from 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine and 1,12-dodecamethylenediamine.
[0100] Advantageously, the diamine X used is C 10 To C 12 Diamines, in particular selected from 1,10-decamethylenediamine, 1,11-undemethylenediamine and 1,12-dodecamethylenediamine.
[0101] The aromatic dicarboxylic acid is advantageously selected from terephthalic acid (denoted as T), isophthalic acid (denoted as I), 2,5-furan dicarboxylic acid and 2,6-naphthalene dicarboxylic acid (denoted as N) or a mixture thereof; in particular, it is selected from terephthalic acid (denoted as T), isophthalic acid (denoted as I) or a mixture thereof.
[0102] Ar'Y represents a unit obtained by polycondensation of an aromatic diamine Ar' and an aliphatic dicarboxylic acid Y, and the aromatic diamine Ar' is selected from, for example, MXD (meta-xylylenediamine) and PXD (para-xylylenediamine).
[0103] MXDY represents a unit obtained by polycondensation of meta-xylylenediamine (MXD) and at least one aliphatic dicarboxylic acid Y.
[0104] PXDY represents a unit obtained by polycondensation of p-xylylenediamine (MXD) and at least one aliphatic dicarboxylic acid Y.
[0105] The at least one C 6 To C 36 The dicarboxylic acid Y may be chosen from adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid and diacids obtained from fatty acids.
[0106] The diacid may be linear or branched. Advantageously, it is linear.
[0107] Advantageously, the at least one dicarboxylic acid Y is C 6 -C 18 The dicarboxylic acid is selected from the group consisting of adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid and octadecanedioic acid.
[0108] Advantageously, the at least one dicarboxylic acid Y is C 6 -C 12 The dicarboxylic acid is selected from the group consisting of adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid and dodecanedioic acid.
[0109] Advantageously, the at least one dicarboxylic acid Y is C 10 -C 12 A dicarboxylic acid and is selected from the group consisting of sebacic acid, undecanedioic acid and dodecanedioic acid.
[0110] Advantageously, the polyamide a) is aliphatic.
[0111] Polyamide b)
[0112] The at least one polyamide b) is as defined for the polyamide a) of layer (I), but is a polyamide having a C / N ratio of less than 10, preferably less than 8, and is different from the polyamide used for layer (I).
[0113] Advantageously, said polyamide b) is aliphatic.
[0114] In one embodiment, the polyamide a) is aliphatic and is selected from PA410, PA510, PA610, PA412, PA512, PA612 and PA6.
[0115] Advantageously, it is chosen from PA410, PA510, PA612 and PA6, in particular PA6.
[0116] Impact modifier c)
[0117] The impact modifier may be present in an amount of up to 30% by weight relative to the total weight of the layer (I) composition.
[0118] In one embodiment, the impact modifier is present in an amount of up to 15 wt. %, in particular up to 12 wt. %, relative to the total weight of the layer (I) composition.
[0119] In another embodiment, the impact modifier is present in an amount of 3 to 30 wt. %, based on the total weight of the layer (I) composition, in particular 3 to 15 wt. %, especially 3 to 12 wt. %, based on the total weight of the layer (I) composition.
[0120] The impact modifier is advantageously composed of a polymer having a flexural modulus of less than 100 MPa, measured according to standard ISO 178:2010, at 23° C., 50% relative humidity RH, and a Tg of less than 0° C. (measured according to standard 11357-2:2013 at the inflection point of the DSC thermogram, heating rate: 20 K / min), in particular a polyolefin.
[0121] The polyolefin of the impact modifier can be functionalized or non-functionalized, or a mixture of at least one functionalized and / or at least one non-functionalized polyolefin. For simplicity, polyolefin is represented by (B), and functionalized polyolefin (B1) and non-functionalized olefin (B2) are described below.
[0122] The non-functionalized polyolefin (B2) is generally a homopolymer or copolymer of an α-olefin or a diene (e.g. ethylene, propylene, 1-butene, 1-octene, butadiene). Examples that may be mentioned include:
[0123] - ethylene homopolymers and copolymers, in particular LDPE, HDPE, LLDPE (linear low-density polyethylene), VLDPE (very low-density polyethylene) and metallocene polyethylene,
[0124] - propylene homopolymer or copolymer,
[0125] - ethylene / α-olefin copolymers, such as ethylene / propylene, EPR (abbreviation for ethylene-propylene rubber) and ethylene / propylene / diene (EPDM) copolymers;
[0126] - styrene / ethylene-butylene / styrene (SEBS), styrene / butadiene / styrene (SBS), styrene / isoprene / styrene (SIS) or styrene / ethylene-propylene / styrene (SEPS) block copolymers;
[0127] - Copolymers of ethylene with at least one product selected from the group consisting of salts or esters of unsaturated carboxylic acids, such as alkyl (meth)acrylates, such as methyl acrylate, or vinyl esters of saturated carboxylic acids, such as vinyl acetate (EVA), in which the proportion of comonomers may be up to 40% by weight.
[0128] The functionalized polyolefin (B1) may be a polymer of an α-olefin with a reactive unit (functional group); such a reactive unit is an acid, anhydride or epoxy functional group. As an example, the aforementioned polyolefin (B2) grafted or copolymerized or terpolymerized with an unsaturated epoxide (e.g. glycidyl (meth)acrylate), or with a carboxylic acid or a corresponding salt or ester (e.g. (meth)acrylic acid, which may be completely or partially neutralized by a metal (e.g. Zn, etc.), or with a carboxylic anhydride (e.g. maleic anhydride) may be mentioned. The functionalized polyolefin is, for example, a PE / EPR mixture, the weight ratio of which may vary within a wide range, for example between 40 / 60 and 90 / 10, said mixture being co-grafted with an anhydride (in particular maleic anhydride), the degree of grafting being, for example, 0.01 to 5% by weight.
[0129] The functionalized polyolefin (B1) can be selected from the following (co)polymers grafted with maleic anhydride or glycidyl methacrylate, where the degree of grafting is, for example, 0.01 to 5% by weight:
[0130] PE, PP, copolymers of ethylene with propylene, butene, hexene or octene, for example containing 35 to 80% by weight of ethylene;
[0131] - ethylene / α-olefin copolymers, such as ethylene / propylene, EPR (abbreviation for ethylene-propylene rubber) and ethylene / propylene / diene (EPDM) copolymers;
[0132] - styrene / ethylene-butylene / styrene (SEBS), styrene / butadiene / styrene (SBS), styrene / isoprene / styrene (SIS) and styrene / ethylene-propylene / styrene (SEPS) block copolymers;
[0133] - copolymers of ethylene and vinyl acetate (EVA) containing up to 40% by weight of vinyl acetate;
[0134] - copolymers of ethylene and alkyl (meth)acrylates containing up to 40% by weight of alkyl (meth)acrylates;
[0135] - Copolymers of ethylene with vinyl acetate (EVA) and alkyl (meth)acrylates containing up to 40% by weight of comonomers.
[0136] The functionalized polyolefin (B1) can also be chosen from ethylene / propylene copolymers, propylene being predominant, which are grafted with maleic anhydride and then condensed with monoamine polyamides (or polyamide oligomers) (products described in EP-A-0342066).
[0137] The functionalized polyolefin (B1) can also be a copolymer or terpolymer of at least the following units: (1) ethylene, (2) an alkyl (meth)acrylate or a saturated carboxylic acid vinyl ester, and (3) an anhydride (e.g. maleic anhydride) or (meth)acrylic acid or an epoxy (e.g. glycidyl (meth)acrylate).
[0138] As examples of functionalized polyolefins of the latter type, mention may be made of the following copolymers, in which ethylene preferably represents at least 60% by weight of the copolymer, and in which the termonomer (functional group) represents, for example, from 0.1% to 10% by weight of the copolymer:
[0139] - ethylene / alkyl (meth)acrylate / (meth)acrylic acid or maleic anhydride or glycidyl methacrylate copolymers;
[0140] - ethylene / vinyl acetate / maleic anhydride or glycidyl methacrylate copolymers;
[0141] - Ethylene / vinyl acetate or alkyl (meth)acrylate / (meth)acrylic acid or maleic anhydride or glycidyl methacrylate copolymers.
[0142] In the above copolymer, (meth)acrylic acid may be salified with Zn or Li.
[0143] The term "alkyl (meth)acrylate" in (B1) or (B2) means methacrylic acid C 1 -C 8 Alkyl esters and acrylic acid C 1 -C 8 Alkyl esters and may be selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, methyl methacrylate and ethyl methacrylate.
[0144] In addition, the above polyolefin (B1) can also be crosslinked by any suitable method or reagent (diepoxide, diacid, peroxide, etc.); the term "functionalized polyolefin" also includes mixtures of the above polyolefins and difunctional reagents that can react with these polyolefins (such as diacids, dianhydrides, diepoxides, etc.), or mixtures of at least two functionalized polyolefins that can react together.
[0145] The above-mentioned copolymers (B1) and (B2) may be copolymerized in a random or block manner, and may have a linear or branched structure.
[0146] The molecular weight, MFI index and density of these polyolefins can also vary over a wide range, as will be known to those skilled in the art. MFI is the abbreviation for melt flow index. It is measured according to standard ASTM 1238.
[0147] Advantageously, the non-functionalized polyolefin (B2) is chosen from polypropylene homopolymers or copolymers, and any ethylene homopolymer, or copolymers of ethylene with higher alpha-olefin type comonomers, such as butene, hexene, octene or 4-methyl-1-pentene. Mention may be made, for example, of PP, high-density PE, medium-density PE, linear low-density PE, low-density PE and very low-density PE. It is known to those skilled in the art that these polyethylenes are prepared according to the "free radical" process, according to the "Ziegler" catalytic process or more recently the so-called "metallocene" catalytic process.
[0148] Advantageously, the functionalized polyolefin (B1) is chosen from any polymer comprising α-olefin units and units carrying polar reactive functional groups, such as epoxy, carboxylic acid or carboxylic anhydride functional groups. Examples of such polymers that may be mentioned include terpolymers of ethylene, alkyl acrylates and maleic anhydride or glycidyl methacrylate, such as products (SKFunctional Polymers); or polyolefins grafted with maleic anhydride, such as products (SK Functional Polymers); and terpolymers of ethylene, alkyl acrylates and (meth)acrylic acid. Mention may also be made of polypropylene homopolymers or copolymers which are grafted with carboxylic anhydrides and then condensed with polyamides or monoamino oligomers of polyamides.
[0149] Additives d)
[0150] The additives may be present in an amount of up to 5% by weight relative to the total weight of the layer (I) composition.
[0151] In one embodiment, the additive is present in an amount of 0.1 to 5 wt % relative to the total weight of the layer (I) composition.
[0152] The additives optionally used in the composition of the invention are the conventional additives used in polyamides well known to those skilled in the art, in particular the additives described in EP 2098580.
[0153] For example, they are selected from catalysts, antioxidants, heat stabilizers, UV absorbers, light stabilizers, lubricants, inorganic fillers, flame retardants, nucleating agents, colorants, reinforcing fibers, waxes and mixtures thereof.
[0154] The term "catalyst" refers to a polycondensation catalyst, such as a mineral acid or an organic acid.
[0155] Advantageously, the proportion by weight of the catalyst is from about 50 ppm to about 5000 ppm, in particular from about 100 ppm to about 3000 ppm, relative to the total weight of the composition.
[0156] Advantageously, the catalyst is selected from phosphoric acid (H 3 PO 4 ), phosphorous acid (H 3 PO 3 ) and hypophosphorous acid (H 3 PO 2 ) or a mixture thereof.
[0157] As an example, the stabilizer may be a UV stabilizer, an organic stabilizer or more generally a combination of organic stabilizers, such as a phenolic antioxidant (such as Ciba-BASF's 245 or 1098 or 1010), phosphite / salt antioxidants (such as Ciba-BASF's 126 and 168), or even optionally other stabilizers, such as HALS, i.e. hindered amine light stabilizers (such as Ciba-BASF's 770), UV stabilizers (such as Ciba's 312) or phosphorus-based stabilizers. Amine antioxidants (e.g. Crompton's 445) or multifunctional stabilizers (such as Clariant's S-EED).
[0158] The stabilizer may also be a mineral stabilizer, such as a copper-based stabilizer. Examples of such mineral stabilizers that may be mentioned include copper acetate and copper halides. Incidentally, other metals, such as silver, may also be considered, but the effects of said metals are known to be less effective. These copper-based compounds are usually combined with halides of alkali metals, in particular potassium.
[0159] For example, the mineral filler is an antistatic filler such as selected from the group consisting of carbon black, graphite, carbon fibers and carbon nanotubes, in particular carbon black and carbon nanotubes.
[0160] Plasticizer e)
[0161] The plasticizer may be present in an amount of 0 to 14 wt. %, relative to the total weight of the layer (I) composition.
[0162] As an example, the plasticizer is selected from benzenesulfonamide derivatives, such as n-butylbenzenesulfonamide (BBSA); ethyltoluenesulfonamide or N-cyclohexyltoluenesulfonamide; hydroxybenzoic acid esters, such as 2-ethylhexyl p-hydroxybenzoate and 2-hexyldecyl p-hydroxybenzoate; tetrahydrofurfuryl alcohol esters or ethers, such as oligoethyleneoxytetrahydrofurfuryl alcohol; and esters of citric acid or hydroxymalonic acid, such as oligoethyleneoxymalonates.
[0163] Mixtures of plasticizers may be used without departing from the scope of the present invention.
[0164] In one embodiment, the plasticizer is present in the composition in an amount of 1 to 14 wt. %, in particular 1 to 12 wt. %, relative to the total weight of the composition of layer (I).
[0165] In another embodiment, the plasticizer is present in an amount of 5 to 14 wt. %, in particular 5 to 12 wt. %, relative to the total weight of the layer (I) composition.
[0166] In one embodiment, the composition of the outer layer (I) consists of:
[0167] a) 41 to 100% by weight of at least one polyamide having a C / N ratio of greater than 7, preferably greater than 8, in particular an aliphatic polyamide,
[0168] b) 0 to 10% by weight of at least one aliphatic polyamide having a C / N ratio of less than 10, preferably less than 8, different from the aforementioned polyamides,
[0169] c) 0 to 30% by weight of at least one impact modifier,
[0170] d) 0 to 5% by weight of at least one additive,
[0171] e) 0 to 14% by weight of at least one plasticizer,
[0172] The sum of components a)+b)+c)+d)+e) equals 100% by weight.
[0173] About Layer (II)
[0174] Layer (II) is a barrier layer which is water-soluble at a temperature of less than or equal to 150°C, in particular less than or equal to 120°C.
[0175] The term "barrier" layer means that the layer has a very low permeability to the fluid being transported.
[0176] The term "barrier layer" refers to a layer that is very low in permeability to fluids, especially fuels, especially alcohol-blended gasoline and hydrogen, so that it allows very little fluid, especially fuels, especially gasoline, especially alcohol-blended gasoline to enter the atmosphere or hydrogen.
[0177] In particular, the term "barrier" refers to the proportion of fuel (especially gasoline, especially alcohol-blended gasoline) entering the atmosphere, when measured with CE 10 fuel at 60°C, less than 150 g.mm / m 2 .day, especially less than 20g.mm / m 2 / sky.
[0178] Gasoline permeability is measured gravimetrically at 60°C using CE10: isooctane / toluene / ethanol = 45 / 45 / 10 vol% and CE85: isooctane / toluene / ethanol = 7.5 / 7.5 / 85 vol% on a plate consisting of a polymer material.
[0179] In particular, the term "barrier layer" means that the layer is impervious to hydrogen at 23°C, i.e., at 0% relative humidity (RH), the permeability to hydrogen at 23°C is less than 500 cc.mm / m 2 .24h.atm. The instantaneous permeability is zero during the induction period and then gradually increases to an equilibrium value, which corresponds to the permeability value under continuous operation conditions. This value obtained under continuous operation conditions is considered to be the permeability of the material.
[0180] The term "water-soluble at a temperature of less than or equal to 150°C, in particular less than or equal to 120°C" means that the polymer in layer (II) is water-soluble below this temperature and in particular has a water solubility greater than 2%, for example in the range of 2% to 100% (mass percentage of polymer in water) at this temperature or below this temperature.
[0181] Ethylene vinyl alcohol (EVOH) is not a water-soluble polymer in the sense of the present invention.
[0182] In one embodiment, the water-soluble polymer has a water solubility of 5% to 20%, especially 10% to 20% at a temperature of 35°C to 150°C, especially 35°C to 120°C, especially 70°C to 150°C, especially 70°C to 120°C.
[0183] The pH value of the aqueous solution used to dissolve layer (II) may be different from 7, but is advantageously between 1 and 12, preferably between 3 and 9.
[0184] The water-soluble polymer may be:
[0185] Natural polymers such as dextrin, casein, dextran, pullulan or based on these elements,
[0186] Man-made polymers: cellulose ethers;
[0187] Synthetic polymers: Vinyl: Polyvinyl alcohol (PVAL), Polyacrylamide.
[0188] In another embodiment, the water-soluble polymer is selected from copolymers containing vinyl alcohol and / or vinyl acetate units (in an amount greater than 50 wt%, such as greater than 70 wt%, preferably greater than 80 wt%) and milk casein-based polymers.
[0189] In a first variant of this embodiment, the water-soluble polymer is a copolymer comprising at least (i) 50% by weight or more of vinyl alcohol units, relative to the total weight of the copolymer, and (ii) 50% by weight or less of olefin units containing at least one heteroatom, relative to the total weight of the copolymer.
[0190] According to this embodiment, the term "olefin units comprising at least one heteroatom" refers to olefin units other than vinyl alcohol units.
[0191] According to this embodiment, the water-soluble polymer is therefore a copolymer comprising at least (i) a content greater than or equal to 50% by weight of vinyl alcohol units, relative to the total weight of the copolymer, and (ii) a content less than or equal to 50% by weight of olefin units comprising at least one heteroatom, relative to the total weight of the copolymer, wherein the olefin units comprise at least one heteroatom different from the vinyl alcohol units.
[0192] The term "heteroatom" is intended to mean an atom other than a carbon atom (C) and a hydrogen atom (H). It may especially be a nitrogen atom (N) or an oxygen atom (O).
[0193] The olefin unit comprising at least one heteroatom may be an olefin unit containing at least one nitrogen and / or oxygen atom.
[0194] According to one embodiment, the term "olefin units comprising at least one heteroatom" refers to olefin units other than vinyl acetate units.
[0195] It may especially be an olefin unit comprising at least one, or even several, alcohol (—OH), amine (—NH 2 ) or carboxylic acid (—COOH) functional groups.
[0196] According to one embodiment, the olefin units comprising at least one heteroatom for the purposes of the present invention typically comprise carbon atoms and heteroatoms in a ratio [number of carbon atoms] / [number of heteroatoms] between 1 and 10, such as between 1.5 and 8, such as greater than 2, such as between 2 and 6.
[0197] According to one embodiment, it may be an olefin unit comprising at least one alcohol function, said unit being not vinyl alcohol. It may especially be an olefin unit comprising at least two alcohol functions. As an example, it may be mentioned a unit derived from an olefin glycol, such as a propylene glycol unit.
[0198] According to another embodiment, it may be an olefin unit comprising at least one amine function, in particular at least two amine functions, such as a butenediamine unit.
[0199] According to another embodiment, it may be an olefin unit comprising at least one carboxylic acid function, in particular at least two carboxylic acid functions.
[0200] According to one embodiment, it may be an olefin unit comprising at least one alcohol function and at least one amine function.
[0201] According to one embodiment, it may be an olefin unit comprising at least one alcohol function and at least one carboxylic acid function.
[0202] According to one embodiment, it may be an olefin unit comprising at least one amine function and at least one carboxylic acid function.
[0203] According to one embodiment, the water-soluble polymer is therefore a copolymer comprising at least (i) a content greater than or equal to 50% by weight of vinyl alcohol units relative to the total weight of the copolymer, and (ii) a content less than or equal to 50% by weight of olefin units comprising at least one heteroatom chosen from nitrogen and oxygen, relative to the total weight of the copolymer, wherein the olefin units comprise at least one heteroatom different from the vinyl alcohol units and the vinyl acetate units.
[0204] According to any embodiment of this first variant, said copolymer may comprise a content greater than or equal to 70% by weight, advantageously greater than or equal to 85% by weight, of said vinyl alcohol units relative to the total weight of said copolymer.
[0205] According to any embodiment of this first variant, said copolymer may comprise a content less than or equal to 30% by weight, advantageously less than or equal to 15% by weight, of said olefin units comprising at least one heteroatom, such as those previously described, relative to the total weight of said copolymer.
[0206] According to any embodiment, the water-soluble polymer may be a copolymer comprising at least one other unit.
[0207] It is worth noting that it can be a copolymer comprising at least (i) vinyl alcohol units in a content greater than or equal to 50% by weight relative to the total weight of the copolymer; (ii) olefin units comprising at least one heteroatom as defined above, wherein the olefin units comprise at least one heteroatom different from the vinyl alcohol units and the vinyl acetate units; and (iii) vinyl acetate units, wherein the olefin units comprising at least one heteroatom and the vinyl acetate units together are present in a content less than or equal to 50% by weight relative to the total weight of the copolymer.
[0208] Preferably, according to this embodiment, the vinyl acetate units are present in a content less than or equal to 20% by weight, such as less than or equal to 15% by weight, such as less than or equal to 10% by weight, such as less than or equal to 5% by weight, typically less than or equal to 1% by weight, relative to the total weight of the copolymer.
[0209] According to any embodiment of this first variant, said water-soluble polymer comprises less than 10% by weight of olefin units of formula CnH2n relative to the total weight of said copolymer.
[0210] In particular, the copolymer may comprise less than 5% by weight, especially less than 1% by weight, of olefin units of formula CnH2n, relative to the total weight of the copolymer.
[0211] According to one embodiment, the water-soluble copolymer does not contain olefin units of formula CnH2n.
[0212] The term "olefin of formula CnH2n" is intended to mean an olefin comprising only carbon and hydrogen atoms.
[0213] According to another embodiment, the water-soluble polymer can be a copolymer composed of: (i) a content greater than or equal to 50% by weight of vinyl alcohol units, relative to the total weight of the copolymer, and (ii) a content less than or equal to 50% by weight of olefin units containing at least one heteroatom, for example chosen from nitrogen and oxygen, relative to the total weight of the copolymer, wherein the olefin units contain at least one heteroatom different from the vinyl alcohol units.
[0214] In a second variant of this embodiment (i.e., the second variant of the aforementioned embodiment, according to which the water-soluble polymer is selected from copolymers comprising vinyl alcohol and / or vinyl acetate units (whose content is greater than 50% by weight, for example greater than 70% by weight, preferably greater than 80% by weight) and milk casein-based polymers), the water-soluble polymer is a copolymer comprising at least one vinyl alcohol unit in a content greater than or equal to 50% by weight and a content less than or equal to 50% by weight of vinyl acetate units, relative to the total weight of the copolymer.
[0215] According to any embodiment of this second variant, the copolymer may comprise a content of greater than or equal to 70% by weight, such as greater than or equal to 80% by weight, such as greater than or equal to 90% by weight, such as greater than or equal to 95% by weight, of vinyl alcohol units relative to the total weight of the copolymer.
[0216] According to any embodiment of this second variant, the copolymer may comprise a content of less than or equal to 30% by weight, such as less than or equal to 20% by weight, such as less than or equal to 10% by weight, such as less than or equal to 5% by weight, of said vinyl acetate units relative to the total weight of the copolymer.
[0217] According to any embodiment of this second variant, the water-soluble polymer may be a copolymer comprising at least one other unit.
[0218] According to any embodiment of this second variant, said water-soluble polymer comprises less than 10% by weight of olefin units of formula CnH2n relative to the total weight of said copolymer.
[0219] In particular, the copolymer may comprise less than 5% by weight, especially less than 1% by weight, of olefin units of formula CnH2n, relative to the total weight of the copolymer.
[0220] According to one embodiment, the water-soluble copolymer does not contain olefin units of formula CnH2n.
[0221] The term "olefin of formula CnH2n" is intended to mean an olefin comprising only carbon and hydrogen atoms.
[0222] According to another embodiment, the water-soluble polymer may be a copolymer consisting of (i) vinyl alcohol units having a content of greater than or equal to 50 wt % and (ii) vinyl acetate units having a content of less than or equal to 50 wt %.
[0223] The presence or ratio of heteroatoms can be determined by carbon NMR in DMSO-d6.
[0224] In another embodiment, the water soluble polymer has a melting point (Tm) of 160°C to 250°C, specifically 165°C to 220°C.
[0225] In one embodiment, layer (II) comprises from 0.1 to 30% by weight, advantageously from 1 to 13.5% by weight, of glycerol, relative to the total weight of said layer (II).
[0226] In one embodiment, the water soluble polymer comprises functional groups reactive with the polyamide, particularly carboxylic acid and primary amine functional groups.
[0227] Tg, Tc and Tm were determined by differential scanning calorimetry (DSC) according to standards 11357-2:2013 and 11357-3:2013, respectively.
[0228] In yet another embodiment, the water-soluble polymer has a transition temperature of 180°C to 250°C, specifically 190°C to 220°C.
[0229] According to one embodiment, the invention relates to a process for manufacturing a multilayer structure as defined according to the invention, comprising at least one step of extruding or injecting said water-soluble polymer at a temperature ranging from 180°C to 250°C, in particular from 190°C to 220°C.
[0230] In one embodiment, the water-soluble polymer of layer (II) does not include ethylene vinyl alcohol (EVOH).
[0231] According to one embodiment, the water-soluble polymer of layer (II) is not ethylene vinyl alcohol (EVOH).
[0232] In particular, it is known practice to convert ethylene vinyl alcohol (EVOH) at temperatures generally below 180°C, usually by extrusion or injection.
[0233] About the inner layer
[0234] The inner layer is a polyamide layer (III), in particular an aliphatic polyamide layer, or a layer (IV) which essentially comprises at least one polyamide.
[0235] In both cases, the layer (III) or (IV) is the layer which is in contact with the fluid being transported.
[0236] The inner layer may also be a layer (IV) adjacent to layer (III). In the latter case, layer (IV) is also adjacent to layer (II), and layer (III) is the innermost layer. In the latter case, layer (III) is the layer in contact with the fluid being transported.
[0237] Regarding the composition of the inner layer (III) (when present)
[0238] The composition of the inner layer (III) comprises:
[0239] a) 41 to 100% by weight of at least one polyamide having a C / N ratio of greater than 7, preferably greater than 8, in particular an aliphatic polyamide,
[0240] b) 0 to 10% by weight of at least one aliphatic polyamide having a C / N ratio of less than 10, preferably less than 8, different from the aforementioned polyamides,
[0241] c) 0 to 30% by weight of at least one impact modifier,
[0242] d) 0 to 5% by weight of at least one additive,
[0243] e) 0 to 14% by weight of at least one plasticizer,
[0244] The sum of components a)+b)+c)+d)+e) equals 100% by weight.
[0245] Components a), b), c), d) and e) are as defined for the composition of layer (I).
[0246] Each of the components a), b), c), d) and e) of the composition of the inner layer (III) may be the same as or different from the components of layer (I).
[0247] In one embodiment, the composition of the inner layer (III) consists of:
[0248] a) 41 to 100% by weight of at least one polyamide having a C / N ratio of greater than 7, preferably greater than 8, in particular an aliphatic polyamide,
[0249] b) 0 to 10% by weight of at least one polyamide, different from the aforementioned polyamides, having a C / N ratio of less than 10, preferably less than 8, in particular an aliphatic polyamide,
[0250] c) 0 to 30% by weight of at least one impact modifier,
[0251] d) 0 to 5% by weight of at least one additive,
[0252] e) 0 to 14% by weight of at least one plasticizer,
[0253] The sum of components a)+b)+c)+d)+e) equals 100% by weight.
[0254] In one embodiment, when inner layer (III) is present, the composition of inner layer (III) is free of plasticizers.
[0255] Regarding the composition of the inner layer (IV) (when present)
[0256] It mainly comprises at least one polyamide of aliphatic type or consisting of more than 75% of aliphatic units, said aliphatic polyamide being chosen from:
[0257] - polyamides, denoted A, whose average number of carbon atoms per nitrogen atom, denoted CA, is from 4 to 8.5, advantageously from 4 to 7;
[0258] - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5;
[0259] - polyamides, denoted C, having an average number of carbon atoms per nitrogen atom, denoted CC, ranging from 9 to 18, advantageously from 10 to 18.
[0260] The aliphatic polyamides denoted A, B and C are as defined for the aliphatic polyamides of the outer layer (I), with the proviso that the average number of carbon atoms per nitrogen atom is followed for each polyamide.
[0261] In one embodiment, the composition of layer (IV) consists essentially of at least one polyamide of aliphatic type or consisting of more than 75% aliphatic units, said aliphatic polyamide being chosen from:
[0262] - polyamides, denoted A, whose average number of carbon atoms per nitrogen atom, denoted CA, is from 4 to 8.5, advantageously from 4 to 7;
[0263] - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5;
[0264] - polyamides, denoted C, having an average number of carbon atoms per nitrogen atom, denoted CC, ranging from 9 to 18, advantageously from 10 to 18.
[0265] In one embodiment, when inner layer (IV) is present, the composition of inner layer (IV) is free of plasticizers.
[0266] In one embodiment, when inner layer (III) and outer layer (IV) are present, the compositions of inner layer (III) and outer layer (IV) do not contain a plasticizer.
[0267] About the structure itself
[0268] The structure comprises at least three layers from outside to inside:
[0269] (I) / / (II) / / (III) or (I) / / (II) / / (IV)
[0270] In one embodiment, the structure further comprises a layer (V) located between layer (I) and layer (II), said layer (V) consisting of a polyamide or a composition mainly comprising at least one aliphatic type consisting of more than 75% aliphatic units, said aliphatic polyamide being selected from:
[0271] - polyamides, denoted A, whose average number of carbon atoms per nitrogen atom, denoted CA, is from 4 to 8.5, advantageously from 4 to 7;
[0272] - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5;
[0273] - polyamides, denoted C, having an average number of carbon atoms per nitrogen atom, denoted CC, ranging from 9 to 18, advantageously from 10 to 18.
[0274] Said at least one polyamide of aliphatic type in said composition of layer (V) is as defined for the polyamide of aliphatic type in said composition of layer (IV).
[0275] Thus, when layers (III) and (IV) are present, the structure may comprise at least four layers from the outside to the inside:
[0276] (I) / / (II) / / (IV) / / (III)
[0277] Or when layer (V) is present, the structure comprises from the outside to the inside:
[0278] (I) / / (V) / / (II) / / (III) or (I) / / (V) / / (II) / / (IV)
[0279] When layers (III) and (IV) are present and when layer (V) is present, the structure may also comprise at least five layers from the outside to the inside:
[0280] (I) / / (V) / / (II) / / (IV) / / (III)
[0281] In a first variant, the structure consists of three layers from the outside to the inside:
[0282] (I) / / (II) / / (III) or (I) / / (II) / / (IV)
[0283] In a second variant, the structure consists of four layers from the outside to the inside:
[0284] (I) / / (II) / / (IV) / / (III) or (I) / / (V) / / (II) / / (III) or (I) / / (V) / / (II) / / (IV)
[0285] In a third variant, the structure consists of five layers from the outside to the inside:
[0286] (I) / / (V) / / (II) / / (IV) / / (III)
[0287] Regardless of the above embodiments or variants, the thickness of layer (II) in the structure is 5% to 30%, preferably 6% to 20%, of the sum of the thicknesses of each layer.
[0288] Advantageously, the structure is selected from a tank, a hose and a pipe.
[0289] In one embodiment, the proportion of extractables determined by the test is at most 1 g / m 2 , especially 0.8g / m 2 Insoluble extractables, the test consists of filling a tubular structure with FAM-B type alcohol blended gasoline and heating the assembly at 60°C for 96 hours and then draining it by filtering it into a beaker.
[0290] Advantageously, the filtrate from the beaker is then allowed to evaporate at room temperature to weigh the residue, which must be less than or equal to about 8 g / m 2 Inner tube surface area, especially 6g / m 2 Inner tube surface area.
[0291] Alcohol-blended gasoline FAM B is described in the standards DIN 51604-1:1982, DIN 51604-2:1984 and DIN 51604-3:1984.
[0292] Briefly, alcohol-blended gasoline FAM A was first prepared with a mixture of 50% toluene, 30% isooctane, 15% diisobutylene and 5% ethanol, and then FAM B was prepared by mixing 84.5% FAM A with 15% methanol and 0.5% water.
[0293] FAM B consists in total of 42.3% toluene, 25.4% isooctane, 12.7% diisobutylene, 4.2% ethanol, 15% methanol and 0.5% water.
[0294] According to another aspect, the invention relates to a composition comprising at least 30% by weight, advantageously 50% by weight, of a multilayer structure as defined above, relative to the total weight of the composition, after recovery by grinding and by washing the ground structure with hot water so as to partially or completely dissolve the water-soluble polymer.
[0295] In one embodiment, after grinding and washing with hot water, the composition comprises less than 5% by weight, advantageously 1% by weight, of said water-soluble polymer relative to the total weight of the composition.
[0296] In one embodiment, the polyamide of the composition comprises functional groups derived from oxidation reactions or reactions with automotive fluids.
[0297] The polyamide comprising functional groups derived from oxidation or reactive with automotive fluids may originate from the outer layer (I) or the inner layer (III) and / or (IV).
[0298] During the use of pipes for conveying or storing fluids in motor vehicles, new species appear in the polyamide constituting the pipe or tank as a result of oxidation mechanisms, in particular amide functional groups and / or methylene groups in the alpha position relative to the amide functional groups, such as imide, carboxylic acid, primary amide and alcohol functional groups.
[0299] The functional groups appear as a result of UV radiation or heating, or as a result of reactions with compounds with which the object has come into contact (eg, gasoline, sunscreen, lubricants, etc.).
[0300] The functional groups can be detected by infrared spectroscopy.
[0301] Therefore, 1700 to 1740 cm -1 The absorption bands correspond to imide, 1680 to 1720 cm -1 The absorption band corresponds to the carbonyl group of carboxylic acid, 3580 to 3670 cm -1 The absorption band corresponds to the alcohol functional group of the carboxylic acid.
[0302] 3580 to 3670cm -1 The absorption band corresponds to the free alcohol functional group.
[0303] The amide functional group is characterized by the presence of 3100 to 3500 cm -1 and 1560 to 1640cm -1 A pair of absorption bands, which correspond to the NH groups of the amide, followed by 1650 to 1700 cm -1 This corresponds to the carbonyl group of the amide.
[0304] In one embodiment, said polyamide of said single-layer and / or multilayer tube intended for conveying automotive fluids, or also of used tubes, carries functional groups resulting from an oxidation reaction, chosen from imide, carboxylic acid and alcohol functional groups and mixtures thereof, in a molar ratio relative to the amide functional groups greater than that of the same polyamide constituting an unused tube that has never conveyed automotive fluids.
[0305] Advantageously, said molar ratio of functional groups resulting from the oxidation reaction relative to secondary amide functional groups is between 1 / 10000 and 1 / 20.
[0306] The concentration can be measured by proton NMR in dichloromethane-d2, where HFIP (hexafluoroisopropanol) is added to dissolve the polyamide.
[0307] In a first variant, the molar ratio of imide functional groups is from 1 / 1000 to 1 / 20, especially from 1 / 500 to 1 / 20, in particular from 1 / 200 to 1 / 50.
[0308] In a second variant, said molar ratio of carboxylic acid functional groups is between 1 / 5000 and 1 / 20, in particular between 1 / 3000 and 1 / 50, very advantageously between 1 / 500 and 1 / 15.
[0309] In a third variant, said molar ratio of alcohol functions is between 1 / 1000 and 1 / 20, advantageously between 1 / 1000 and 1 / 25 and very advantageously between 1 / 200 and 1 / 50.
[0310] In a fourth variant, the molar ratio of primary amide functions relative to secondary amide functions is between 1 / 2000 and 1 / 20, advantageously between 1 / 1000 and 1 / 100 and very advantageously between 1 / 10 000 and 1 / 500.
[0311] In a fifth variant, the molar ratio of nitrile functions relative to secondary amide functions is between 1 / 1000 and 1 / 20, advantageously between 1 / 500 and 1 / 15 and very advantageously between 1 / 100 and 1 / 10.
[0312] In a sixth variant, the molar ratio of chain-end methyl functions relative to secondary amide functions is from 1 / 5000 to 1 / 50, advantageously from 1 / 2000 to 1 / 100 and very advantageously from 1 / 1000 to 1 / 200.
[0313] It will be apparent that as a single layer and / or multilayer tube intended for conveying automotive fluids, or even a used tube, and the exposed functional groups it will experience, there may be one or more functional groups resulting from oxidation reactions.
[0314] The composition also advantageously comprises a stabilizer residue selected from phenols, quinones, stilbenequinones and phosphites.
[0315] The recycled polyamide advantageously contains alkyl chain ends having a carbon number (1 to 18) greater than that of the virgin PA. Advantageously, the alkyl chain end content is between 1 ppm and 0.5%.
[0316] The used polyamide in the composition is more crystalline than the original polyamide.
[0317] The percentage of crystallinity can be measured by DSC (or X-ray).
[0318] Advantageously, the crystallinity of the used polyamide is at least 2%, in particular at least 5%, greater than the crystallinity of the virgin polyamide, as measured by DSC.
[0319] According to another aspect, the invention relates to a method for recovering a structure as defined above, characterized in that it comprises the steps of grinding said structure and then washing it with hot water to dissolve and at least partially remove the water-soluble polymer from said structure, thereby obtaining the other components of said structure.
[0320] The temperature of the hot water is 70°C to 150°C, particularly 70°C to 120°C.
[0321] Hot water can have a pH between 1 and 12.
[0322] In one embodiment, the method comprises the step of extruding or injecting the other components of the structure.
[0323] In one embodiment, the method comprises a blending step prior to extrusion or injection.
[0324] This blending step allows the addition of impact modifiers and / or additives and / or plasticizers.
[0325] In another embodiment, the injection or extrusion step allows for the creation of further tanks, hoses or tubes. Example
[0326] The invention will now be described in more detail by way of the following non-limiting examples.
[0327] The following structures were prepared by extrusion:
[0328] The multilayer tubes were prepared by coextrusion using a McNeil Industrial multilayer extrusion line (equipped with five extruders connected to a multilayer extrusion head with a spiral mandrel).
[0329] The screws used are single extrusion screws with a screw profile suitable for polyamide. In addition to the five extruders and the multilayer extrusion head, the extrusion line also includes:
[0330] - a die-punch assembly, located at the end of the coextrusion head; the choice of the die internal diameter and the punch external diameter depends on the structure to be manufactured and its constituent materials, as well as on the size of the tube and the line speed;
[0331] - a vacuum tank with adjustable vacuum level. Water, generally maintained at 20°C, circulates in this tank, in which a measuring instrument is immersed in order to make the tube conform to its final dimensions. The diameter of this measuring instrument is adapted to the dimensions of the tube to be manufactured, and is generally between 8.5 and 10 mm for a tube with an external diameter of 8 mm and a thickness of 1 mm;
[0332] - a series of cooling tanks, in which the water is maintained at about 20°C, used to cool the tube along its path from the extrusion head to the stretching table;
[0333] -Diameter measuring instrument;
[0334] -Stretching table.
[0335] A five-extruder configuration is used to produce tubes with two to five layers. In the case of structures with fewer than five layers, several extruders are fed with the same material.
[0336] In the case where the structure comprises six layers, an additional extruder is connected and a spiral mandrel is added to the existing extrusion head to produce the inner layer in contact with the fluid.
[0337] Prior to testing, to ensure optimal performance and good extrusion quality of the tube, it is verified that the residual moisture content of the extruded material before extrusion is less than 0.08%. If this is not the case, a step of drying the material overnight at 80°C in a vacuum desiccator is usually performed before testing.
[0338] After the extrusion parameters have stabilized, a tube meeting the characteristics described in this patent application is taken, and the target size of the tube no longer changes over time. The diameter is monitored by a laser diameter measuring instrument installed at the end of the production line.
[0339] The production line speed is 20m / min.
[0340] The speed of the extruder screw depends on the thickness of the layer and the screw diameter, as known to those skilled in the art.
[0341] In general, the temperature of the extruder and tooling (extrusion head and connectors) should be set sufficiently above the melting point of the composition in question to keep it molten, thereby preventing it from solidifying and clogging the machine.
[0342] The prepared tubular structures (Table 1) were tested with respect to recyclability parameters (Table 2) according to the following protocol:
[0343] The extruded structures were exposed to CE85 gasoline for 500 hours at 60° C. to simulate gasoline line applications. After this conditioning, they were ground and washed in water at 85° C. for 5 hours, with a mass ratio of ground material to water of 50%.
[0344] The extruded structures were also exposed to hydrogen at 23°C / 0%RH for 168 hours to simulate storage applications. After this conditioning, they were ground and washed in water at 85°C for 5 hours, with a mass ratio of ground material to water of 50%.
[0345] After this conditioning, they were ground and washed in water at 85°C for 5 hours, the mass ratio of ground material to water being 50%.
[0346] The results obtained after exposure to gasoline and hydrogen are identical. The individual mass loss values (wt %) are reported in Table 2.
[0347] CE85 gasoline and hydrogen permeation measurements are performed according to the following protocol:
[0348] The gasoline permeation measurement consists of placing CE85 gasoline in the structure and then sealing the assembly. The assembly is then placed in an ATEX chamber conditioned at 60°C. Regular weighing allows the determination of the amount of gasoline vapor that diffuses through the structure. A weight loss curve is plotted as a function of time for a 500 hour test and the permeability coefficient is determined from the slope of the weight loss curve and the surface area of the sample (Scheme 1).
[0349] The hydrogen flow at 23° C. and 0% RH was determined according to standard ISO 15105-2 (Scheme 2).
[0350] The quality of good recyclability was evaluated gravimetrically by estimating the mass loss of the ground material before and after washing. This mass loss was mainly attributed to the water-soluble polymers.
[0351] Example Structure CE1 <![CDATA[PA11 a / EVOH / PA11 a (425 / 150 / 425)]]> EI 1 <![CDATA[PA11 a / PVOH * / PA11 a (425 / 150 / 425)]]> CE2 <![CDATA[PA11 a / Tieflex / EVOH / Tieflex(150 / 350 / 100 / 400)]]> EI2 <![CDATA[PA11 a / Tieflex / PVOH * / Tieflex(150 / 350 / 100 / 400)]]> CE3 <![CDATA[PA11 a / Tieflex / EVOH / Tieflex / PA11 a (150 / 400 / 150 / 150 / 150)]]> EI 3 <![CDATA[PA11 a / Tieflex / PVOH * / Tieflex / PA11 a (150 / 400 / 150 / 150 / 150)]]> EI 4 <![CDATA[PA11 a / Tieflex / PVOH ** / Tieflex / PA11 a (150 / 400 / 150 / 150 / 150)]]> EI 5 <![CDATA[PA11 b / PVOH * / PA11 b (425 / 150 / 425)]]> EI 6 <![CDATA[PA12 / PVOH * / PA12(425 / 150 / 425)]]> EI 7 <![CDATA[PA11 a / PPVOH / PA11 a (425 / 150 / 425)]]>
[0352] [Table 2]
[0353]
[0354] CE 1 to 3: Counterexample
[0355] EI 1 to 7: Embodiments of the present invention
[0356] The values in brackets in Table 1 correspond to the thickness of each layer (in μm). The density is close to 1.
[0357] EVOH: Kuraray's LA107B grade
[0358] PVOH * : Kuraray's Mowiflex H15 grade, containing 97% by weight of vinyl alcohol units
[0359] PVOH ** : Kuraray's Mowiflex C30 grade, containing 79% by weight of vinyl alcohol units
[0360] PPVOH: a copolymer comprising 90 wt. % vinyl alcohol units and 10 wt. % propylene glycol units Tieflex: a composition comprising 80 wt. % PA6 Ultramid B40 (BASF), 5 wt. % PA610 with an Mn of 27,000 g / mol, 5 wt. % PA11 with an Mn of 25,000 g / mol, and 10 wt. % Orevac IM 800 impact modifier (SK Functional Polymers)
[0361] PA11 a : PA11 with Mn of 25000 g / mol and containing 10 wt% of Orevac IM 800 impact modifier (SK Functional Polymers)
[0362] PA11 b :PA11 with Mn of 25000 g / mol
[0363] PA12: PA12 with Mn of 25000 g / mol and containing 10 wt% of Orevac IM 800 impact modifier (SK Functional Polymers)
[0364] Scheme 1 and Scheme 2 defined in Table 2 correspond to the experimental conditions of the penetration test.
[0365] Solution 1: CE85 gasoline, at 60°C, for 500 hours
[0366] Protocol 2: Hydrogen, at 23°C, for 168 hours. A mass loss of more than 5% (of the total tube mass) means that at least one third (30 wt%) of the barrier layer has dissolved during recycling and therefore the recycled polyamide will be of higher quality.
Claims
1. A recyclable multilayer structure for transporting, distributing or storing fluid, in particular for distributing or storing fluid, comprising from outside to inside: 1) An outer layer (I) made of polyamide, in particular aliphatic polyamide, comprising a composition comprising: a) 41 to 100% by weight of at least one polyamide having a C / N ratio of greater than 7, preferably greater than 8, in particular an aliphatic polyamide, b) 0 to 10% by weight of at least one polyamide, different from the aforementioned polyamides, having a C / N ratio of less than 10, preferably less than 8, in particular an aliphatic polyamide, c) 0 to 30% by weight of at least one impact modifier, d) 0 to 5% by weight of at least one additive, e) 0 to 14% by weight of at least one plasticizer, The sum of the components a) + b) + c) + d) + e) is equal to 100% by weight; 2) a barrier layer (II) which is water-soluble at a temperature of less than or equal to 150° C., in particular less than or equal to 120° C.; 3) Inner layer (III): It is made of polyamide, in particular aliphatic polyamide, comprising a composition comprising: a) 41 to 100% by weight of at least one aliphatic polyamide having a C / N ratio greater than 7, preferably greater than 8, b) 0 to 10% by weight of at least one polyamide, different from the aforementioned polyamides, having a C / N ratio of less than 10, preferably less than 8, in particular an aliphatic polyamide, c) 0 to 30% by weight of at least one impact modifier, d) 0 to 5% by weight of at least one additive, e) 0 to 14% by weight of at least one plasticizer, The sum of the components a) + b) + c) + d) + e) is equal to 100% by weight; and / or (IV) comprising essentially at least one polyamide of aliphatic type or consisting of more than 75% of aliphatic units, said aliphatic polyamide being selected from: - polyamides, denoted A, whose average number of carbon atoms per nitrogen atom, denoted CA, is from 4 to 8.5, advantageously from 4 to 7; - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5; - polyamides, denoted C, whose average number of carbon atoms per nitrogen atom, denoted CC, ranges from 9 to 18, advantageously from 10 to 18; Layer (IV) is adjacent to layer (II) if layer (III) is also present and layer (III) is the innermost; or if layer (III) is not present, layer (IV) is the innermost.
2. The recyclable multilayer structure according to claim 1, wherein: The barrier layer (II) which is water-soluble at a temperature of less than or equal to 150°C, in particular less than or equal to 120°C, is made of a water-soluble polymer selected from copolymers and casein-based polymers containing vinyl alcohol and / or vinyl acetate units in an amount greater than 50% by weight, for example greater than 70% by weight, preferably greater than 80% by weight.
3. The recyclable multilayer structure according to any one of claims 1 and 2, characterized in that The water-soluble polymer is a copolymer comprising at least (i) 50% by weight or more of vinyl alcohol units, relative to the total weight of the copolymer, and (ii) 50% by weight or less of olefin units containing at least one heteroatom, relative to the total weight of the copolymer.
4. The recyclable multilayer structure according to the preceding claim, characterized in that Said copolymer comprises a content of vinyl alcohol units greater than or equal to 70% by weight, advantageously greater than or equal to 85% by weight, relative to the total weight of said copolymer.
5. The recyclable multilayer structure according to any one of claims 3 and 4, characterized in that Said copolymer comprises a content less than or equal to 30% by weight, advantageously less than or equal to 15% by weight, of said olefin units comprising at least one heteroatom, relative to the total weight of said copolymer.
6. The recyclable multilayer structure according to any one of claims 1 and 2, characterized in that The water-soluble polymer is a copolymer comprising at least one vinyl alcohol unit in an amount greater than or equal to 50% by weight and at least one vinyl acetate unit in an amount less than or equal to 50% by weight, relative to the total weight of the copolymer.
7. The recyclable multilayer structure according to claim 6, wherein: The water-soluble polymer comprises the vinyl alcohol units in an amount greater than or equal to 70 wt%, such as greater than or equal to 80 wt%, such as greater than or equal to 90 wt%, such as greater than or equal to 95 wt%, relative to the total weight of the copolymer.
8. The recyclable multilayer structure according to claim 6 or 7, characterized in that: The water-soluble polymer comprises less than or equal to 30 wt %, such as less than or equal to 20 wt %, such as less than or equal to 10 wt %, such as less than or equal to 5 wt % of the vinyl acetate units, relative to the total weight of the copolymer.
9. The recyclable multilayer structure according to any one of claims 1 to 8, characterized in that The water-soluble polymer has a melting point of 160°C to 250°C, specifically 165°C to 220°C.
10. The recyclable multilayer structure according to any one of claims 1 to 9, characterized in that The water-soluble polymer has a transition temperature of 180°C to 250°C, specifically 190°C to 220°C.
11. The recyclable multilayer structure according to any one of claims 1 to 10, characterized in that The water-soluble polymer has a water solubility of 5% to 20%, especially 10% to 20%, at a temperature of 35°C to 150°C, especially 70°C to 150°C.
12. The recyclable multilayer structure according to any one of claims 1 to 11, characterized in that Layer (V) is present between layer (I) and layer (II), said layer (V) consisting of a composition comprising mainly at least one polyamide of aliphatic type or consisting of more than 75% of aliphatic units, said aliphatic polyamide being chosen from: - polyamides, denoted A, whose average number of carbon atoms per nitrogen atom, denoted CA, is from 4 to 8.5, advantageously from 4 to 7; - polyamides, denoted B, whose average number of carbon atoms per nitrogen atom, denoted CB, is from 7 to 10, advantageously from 7.5 to 9.5; - polyamides, denoted C, having an average number of carbon atoms per nitrogen atom, denoted CC, ranging from 9 to 18, advantageously from 10 to 18.
13. The recyclable multilayer structure according to any one of claims 1 to 11, characterized in that It consists of three layers from outside to inside: (I) / / (II) / / (III) or (I) / / (II) / / (IV) 14. The recyclable multilayer structure according to any one of claims 12 and 13, characterized in that It consists of four layers from outside to inside: (I) / / (V) / / (II) / / (III) or (I) / / (V) / / (II) / / (IV) 15. The recyclable multilayer structure according to any one of claims 12 and 13, characterized in that It contains five layers from outside to inside: (I) / / (V) / / (II) / / (IV) / / (III) 16. The recyclable multilayer structure according to any one of claims 1 to 15, characterized in that The thickness of layer (II) in the structure is 5% to 30%, preferably 6% to 20%, of the sum of the thicknesses of each layer.
17. The recyclable multilayer structure according to any one of claims 1 to 16, characterized in that It is selected from a tank, a hose and a tube.
18. A composition comprising at least 30% by weight, advantageously 50% by weight, of a multilayer structure as defined in any one of claims 1 to 17, relative to the total weight of the composition, after recovery by grinding and by washing the ground structure with hot water so as to partially or completely dissolve the water-soluble polymer.
19. The composition of claim 18, comprising less than 5% by weight of water-soluble polymer, in particular less than 1% by weight of water-soluble polymer.
20. A method for recycling a structure as defined in any one of claims 1 to 17, characterized in that The method comprises the steps of grinding the structure and then washing it with hot water to dissolve and at least partially remove the water-soluble polymer in the structure, thereby obtaining the other components of the structure.
21. The method of claim 20, wherein: The method comprises the step of extruding or injecting the other components of the structure.
22. The method according to claim 21, characterized in that The blending step is performed before the injection or extrusion step.
23. The method according to claim 21 or 22, characterized in that The injection or extrusion step allows obtaining a further tank, a further hose or a further tube.
Citation Information
Patent Citations
Graft copolymer on the basis of alpha-mono-olefin, its process of fabrication, its application for the fabrication of thermoplastic blends, thermoplastic blends obtained
EP0342066A1
Adhesive composition and structure comprising at least one layer of said composition.
EP2098580A1
Fluid transfer multi-layer tube based on a polyamide and an ethyl vinyl alcohol or polyvinyl alcohol
WO2008057763A2
Film having liquid-water, grease, gas and water-vapour barrier properties
WO2009083525A1
Fluid transfer multi-layer tube based on a polyamide and an ethyl vinyl alcohol or polyvinyl alcohol
US20100062201A1